Aplikasi Teknologi Telenursing dalam Mencegah Readmisi Pasien Penyakit Kronik - Natallina Sianturi; Rr. Tutik Sri Hariya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to determine whether telenursing applications can prevent the readmission of chronic disease patients at the hospital. This research used the literature review method, which discussed the topic of telenursing technology applications using the keywords readmission and telenursing in English and Spanish between 2017 and 2022. The results showed a review of 10 journals that telenursing effectively prevented hospital readmission in patients with chronic diseases. This system can also increase patient trust in nurses, satisfaction, and quality of life. In conclusion, telenursing can increase patient trust in nurses, increase patient satisfaction, improve patient quality of life and prevent readmissions. Keywords: Chronic Disease, Reading mission, Telenursing